A rapid and sensitive recombinase aided amplification assay incorporating competitive internal control to detect Bordetella pertussis using the DNA obtained by boiling. (September 2019) - Zhang, Rui-qing; Li, Gui-xia; Li, Xin-na; Shen, Xin-xin; Gao, Yuan; Wang, Le; Fan, Tao; Duan, Qing-xia; Wang, Ya-kun; Wang, Ji; Feng, Zhi-shan; Ma, Xue-jun
Highlights: Pertussis is a highly transmissible acute respiratory infection. We present an RAA assay to detect B. pertussis using the DNA obtained by boiling. This assay was performed in a single closed tube at 39 °C within 30 min. The sensitivity of the RAA assay was 10 1 copies or 10 CFU/ml per reaction. The introduction of IAC effectively reduced the occurrence of false negatives. Abstract: Objectives: Pertussis is a highly transmissible acute respiratory infection caused by the bacterial pathogen Bordetella pertussis. The purpose of this study was to develop a rapid, simple and sensitive diagnostic test for detecting this pathogen. Methods: Here we present a recombinase aided amplification (RAA) assay incorporating competitive internal amplification control (IAC) to detect Bordetella pertussis using the DNA obtained by boiling. This assay was performed in a single closed tube at 39 °C within 30 min. A total of 115 clinical samples suspected of pertussis were collected and tested by the internally controlled RAA assay using both extracted DNA with the commercial kit and the DNA obtained by boiling. For comparison, the real-time PCR (RT-PCR) was also performed with DNA extraction in parallel. Results: The sensitivity of the internally controlled RAA assay was 10 1 copies or 10 CFU/ml per reaction in detecting plasmid DNA or B. pertussis strain. The optimum concentration of the IAC plasmid was determined to be 100 copies, and the introduction of IAC effectively reduced the occurrence of false negatives. Compared to the RT-PCR, RAA results with DNA extraction obtained 100% sensitivity and specificity, and the RAA results with heat-treated DNA showed 85.96% sensitivity and 100% specificity. Conclusion: With the advantages of 45 min turn-around time and simple steps of DNA purification, this assay could become a useful diagnostic tool for Bordetella pertussis detection and is potentially suitable for point-of-care identification to guide prompt clinical treatment.